3x - 5y = y - mx
x (3 + m) = 6y
x = 6y / (m + 3)
is this what you wanted?
2006-12-26 04:14:05
·
answer #1
·
answered by Crazy Malamute 3
·
0⤊
1⤋
3x - 5y = y - mx
add mx+5y to both sides of the equation
3x - 5y + mx + 5y = y - mx + mx + 5y
Rearrange in case the next bit isn't obvious
3x+ mx + 5y - 5y = y + 5y + mx - mx
Add the terms (cancelling out some of them)
(3 + m) x = 6y
Divide both sides by (3 + m) [only allowed if m is not equal to -3, division by zero is barred]
x = 6y/(3 + m)
2006-12-26 12:17:57
·
answer #2
·
answered by Dr Bob UK 3
·
0⤊
1⤋
Put all the x's on one side of the equation and all the y's on the other. Then factorise out the x's so x is on its own and divide the y side by the factor multiplying the x's.
3x - 5y = y - mx
3x + mx = 6y
x(3+m) = 6y
x = 6y/(3+m)
2006-12-27 05:15:03
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
1) Take the x's together on the left and the y's on the right:
3x+mx=y+5y.......so 3x+mx=6y Then factorise the left:
x(3+m) = 6y
so x = 6y/(3+m)
2006-12-26 14:03:02
·
answer #4
·
answered by Anonymous
·
0⤊
1⤋
I'm guessing you want to solve for x? If so, I would do...
3x+mx=y+5y
(3+m)x=6y
x=6y/(3+m)
2006-12-26 12:15:02
·
answer #5
·
answered by Stargazing 1
·
0⤊
1⤋
3x-5y=y-mx
3x + mx = y + 5y
x (3 + m) = 6y
x = 6y / (3 + m)
<><
2006-12-26 13:06:52
·
answer #6
·
answered by aeiou 7
·
0⤊
1⤋
X=6y/(3+m)
2006-12-26 12:14:46
·
answer #7
·
answered by Oldbeard 3
·
0⤊
1⤋
3x-5y=y-mx
=3x+mx=6y
=x(3+m)=6y
=x=6y/3+m
hope it helps!!
2006-12-26 12:49:45
·
answer #8
·
answered by Kwunbob 2
·
0⤊
1⤋
3x-5y=y-mx
3x+mx=6y
3x=6y-mx
x=(6y-mx)/3
2006-12-26 12:18:19
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋
3x-5y=y-mx
3x+mx=y+5y
x(3+m)=6y
x=6y/(3+m)
2006-12-26 12:15:16
·
answer #10
·
answered by Gayan K 1
·
0⤊
1⤋